Antimicrobial susceptibility pattern and mupirocin resistance among methicillin-resistant Staphylococcus aureus isolated from skin and soft-tissue infection patients attending a tertiary care hospital in North India - Bajarangi Lal Chaudhary,; Sanjeev Sahai, (Asian Journal of Medical Sciences, 2024)
Background: Antimicrobial susceptibility among bacterial isolates varies from center to center. Mupirocin is a topical antibacterial antibiotic used to treat wound infections caused by methicillin-resistant Staphylococcus aureus (MRSA). Aim and Objectives: This study was conducted to know the prevalence of high and low levels of mupirocin resistance along with antimicrobial susceptibility in MRSA isolates from skin and soft-tissue infection in patients admitted to a tertiary care hospital in North India. Materials and Methods: A total of 97 non-repetitive isolates of MRSA from various pus samples over a period of 1 year were included in this study. These strains were identified as per standard laboratory protocols given by the Clinical Laboratory Standards Institute. High- and low-level mupirocin resistance of the isolates was tested by using mupirocin discs of 200 μg and 5 μg, respectively. Mupirocin strips of 256 μg and 512 μg were used for the E-test to detect low-level and high-level mupirocin resistance, respectively. The isolates were reported as sensitive to mupirocin, with minimum inhibitory concentrations of <4 mg/L. Results: Overall, 9.27% of mupirocin resistance was found, of which 2.06% of isolates were high-level resistant to mupirocin, while 7.21% had low-level resistance. All MRSA strains were susceptible to vancomycin, followed by linezolid (94.84%), teicoplanin (91.75%), and fusidic acid (88.65%). Conclusion: Regular monitoring, good infection control practices, and proper awareness about utilizing mupirocin therapeutically and prophylactically may help prevent the emergence of mupirocin resistance in health-care facilities.